Multifocal myoclonus as a presentation of levetiracetam toxicity - Mei Bou Nasif (Elsevier, 2021)
Background: Levetiracetam (LEV) is widely used for treatment of focal and myoclonic seizures, but reports of LEV toxicity are scarce. Here, we report a rare case of multifocal myoclonus due to LEV toxicity in a patient with chronic renal insufficiency. Case presentation: A 52-year-old woman with history of chronic kidney disease was admitted to the ICU for sedation and intubation after a cardiac arrest. She developed nonconvulsive status epilepticus that resolved after administration of propofol while receiving LEV 1500 mg twice a day. After holding the propofol infusion, the patient started having multifocal myoclonic jerks, documented on video-EEG recordings with a supratherapeutic level of LEV. After discontinuation of LEV, the myoclonus resolved. Conclusion: This is a unique manifestation of LEV toxicity, which has been scarce in the literature. It suggests an inverted U-shaped dose–response of the antimyoclonic effect of LEV.